Optical Cryoimaging of Celular Redox in Kidneys from Diabetic Mice - (:unkn) unknown (My University, 2012)
Diabetic Nephropathy (DN) is the major single cause of end stage renal diseases (ESRD) in the United States. Diabetes is the third leading fatal disorder after cancer and heart disease. It is affecting 8.3% of the residents of the United States, with a total healthcare cost of $174 billion/yr by 2010. There currently exists a need for a sensitive and specific diagnosis for temporal detection of oxidative stress (OS) in cellular metabolic levels, which plays an early role in the development of DN. The objective of this research is to use a fluorescence optical imaging technique in order to delineate temporal and spatial distribution of OS and to evaluate mitochondrial redox state in rodents kidney tissue during diabetes progression. In this research, I investigated whether changes in the metabolic state can be used as a quantitative marker of OS progression in kidneys. Through the monitoring of autofluorescent mitochondrial metabolic coenzymes (NADH, FAD), the redox state of mitochondria can be probed in many intact organs. I have applied a device called cryoimager to measure the fluorescence intensity of these fluorophores simultaneously in 3-D. The ratio of these fluorophores, referred to as the NADH redox ratio (RR), can be used as a quantitative metabolic marker of tissue. I examined redox states of kidneys from diabetic mice, Akita/+, Akita/+; TSP1-/- (Akita mice lacking thrombospondin-1, TSP1) with increasing duration of diabetes, and kidneys from bcl-2-deficient mice. We detected OS shortly after the onset of diabetes by NADH RR, which increased during progression of diabetes. RR indicates a more reduced biochemical state in kidneys from diabetic mice compared with kidneys from wilde type (control) mice. Thus, cryo fluorescence redox imaging showed a quantitative marker of OS progression in kidneys from diabetic mice and demonstrated that alterations in the oxidative state of kidneys occur at different stages of diabetes.
Keywords: Cellular Redox; Cryoimaging; Diabetes; Kidney; Mitochondria; Oxidative Stress